Koto Pulai as the Regency Government Center Pesisir Selatan Kerinci in 1949 - Kaminus Kaminus; Azmi Fitrisia (Pascasarjana, Universitas Negeri Padang, 2019)
The establishment of an emergency government in the Regency of Pesisir Selatan Kerinci was the result of instructions from the Rasjid Resident as Governor of Meliter, West Sumatra, where the Governor of Rasjid sent several delegates of the Governor's staff to the regions. History of the Government of the South Coastal Regency of Kerinci on January 2, 1949 in Koto Pulai, Lengayang Regency (Kambang), the government of the Pesisir Selatan of Kerinci ended on July 14, 1950. Based on the findings and also the author's initial interview with Mr. Anwar AM, he said that many generations did not know its history, even its removal was no longer maintained even though it was protected by cultural heritage and functioned as it should. There is no explanation of the role of the community and the government of the Pesisir Selatan Regency of Kerinci in defending the independence of the Republic of Indonesia from the threat of Dutch military aggression II, no one has examined either the published books or other scientific works. Therefore, that history is not forgotten, and also the legacy of the Government of the Pesisir Selatan of Kerinci in Koto Pulai treated and functioned as it should. Historical research methods, in this study data collection, is done by observation, interviews, and documentation. Observation is to see firsthand the relics of the government of the Pesisir Selatan Regency of Kerinci (PSK), as well as taking pictures of the relics. Interviews in this study include Mr. RusliNur, Anwar Am, Iyal, Syafrial, and Supardi. Documentation is the search for documents and books related to the governance of CSWs. Koto Pulai is a strategic area that is in a cross position, with a very strategic location that makes it easy to deal with fellow warlords in thePesisir Selatan, both warlords who come from Tapan or the Shadows. Koto Pulai is also a fertile area, making it very easy to meet daily needs. The people there are trying to meet all the needs of the PDRI fighters without having to be paid, they do so because the people of Pesisir Selatan in general Koto Pulai have a sense of nationalism and a spirit of patriotism towards the Indonesian people.